2009
DOI: 10.1007/s11671-009-9431-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Docetaxel-Loaded Poly (ε-Caprolactone)/Pluronic F68 Nanoparticle Overcoming Multidrug Resistance for Breast Cancer Treatment

Abstract: Multidrug resistance (MDR) in tumor cells is a significant obstacle to the success of chemotherapy in many cancers. The purpose of this research is to test the possibility of docetaxel-loaded poly (ε-caprolactone)/Pluronic F68 (PCL/Pluronic F68) nanoparticles to overcome MDR in docetaxel-resistance human breast cancer cell line. Docetaxel-loaded nanoparticles were prepared by modified solvent displacement method using commercial PCL and self-synthesized PCL/Pluronic F68, respectively. PCL/Pluronic F68 nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 37 publications
3
77
2
2
Order By: Relevance
“…[14][15][16][17] However, in recent studies by Zhang et al, 16 blank Pluronic P123/F127 mixed polymeric micelles were demonstrated to be toxic at relatively low concentrations (0.1% w/v) compared to the copolymers investigated in this study, which do not induce cytotoxicity below 1% w/v. We suggest that the greater cellular biocompatibility along with the biodegradability of MePEG-b-PCL may be a potential advantage, allowing for higher dosing of drug and copolymer.…”
Section: Cytotoxicity Of Ptx-loaded Nanoparticlescontrasting
confidence: 56%
See 1 more Smart Citation
“…[14][15][16][17] However, in recent studies by Zhang et al, 16 blank Pluronic P123/F127 mixed polymeric micelles were demonstrated to be toxic at relatively low concentrations (0.1% w/v) compared to the copolymers investigated in this study, which do not induce cytotoxicity below 1% w/v. We suggest that the greater cellular biocompatibility along with the biodegradability of MePEG-b-PCL may be a potential advantage, allowing for higher dosing of drug and copolymer.…”
Section: Cytotoxicity Of Ptx-loaded Nanoparticlescontrasting
confidence: 56%
“…13 This led to several reports evaluating multicomponent or mixed polymeric nanoparticles incorporating one or more Pluronics for both solubilizing taxanes and inhibiting P-gp function. [14][15][16][17] However, the potential drawback of using Pluronics is the nondegradability and lack of renal excretion for high-molecular-weight members of this copolymer class. 18,19 Previous work by our group has demonstrated that a very low-molecular-weight MePEG-b-PCL copolymer (MePEG 17 -b-PCL 5 [PCL5]) is an effective modulator of P-gp.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the obviously enhanced cytotoxicity of MTX via the nano-sized particles means that there was a significant reverse effect of drug resistance. NPs could reduce the MDR that characterizes many anticancer drugs by a mechanism of cell internalization of the drug by endocytosis [42], by lowering drug efflux from the cells [43] and/or by allowing pH-dependent drug release from the endosomes to cell cytosol [44]. As demonstrated in Section 3.5, the pH-sensitivity of NPs allowed their rapid escape from the endosomal compartment, which may enhance their therapeutic efficiency compared to the native drug.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In addition, from the zeta potential measurement, we can estimate the dominant component on the particles' surface. 33 The zeta potential of the drug loaded PCEP NPs, LPNPs, and FLPNPs (Table 1) indicates the negative charges on the nanoparticle surface. LPNPs and FLPNPs showed higher negative zeta potential value than that of PCEP NPs.…”
Section: Characterization Of the Nanoparticlesmentioning
confidence: 99%